The Effect of Reward and Punishment, Teacher Readiness, Utilization of Information and Communication Technology on Student Achievement - Irham Abdul Haris; Nyayu Khodijah; Abdurrahmansyah Abdurrahmansyah (AL-ISHLAH: Jurnal Pendidikan, 2021)
The study aimed to determine the effect of the reward and punishment method, teacher readiness, and the use of information and communication technology on student achievement in the Akidah Akhlak subject at Madrasah Aliyah Hidayatul Mubtadiin Jati Agung, South Lampung Regency. The research was quantitative. The population in the study was 235 students with a random sampling technique. The sample used was 235 students. The data collection method used was a questionnaire. The method of data analysis was done by descriptive analysis and path analysis. The study showed that the reward and punishment method positively affected student learning achievement by 19.20%. Second, teacher readiness positively affected student achievement by 26.5%. Third, information and communication technology positively affected student achievement by 29.1%. Fourth, the method of reward and punishment, teacher readiness, and the use of information and communication technology simultaneously positively affected student learning achievement by 36.7%. Thus, teachers were expected to use the reward and punishment method, prepare themselves, and utilize information and communication technology to affect student achievement positively.